2006
DOI: 10.1042/bst0340671
|View full text |Cite
|
Sign up to set email alerts
|

The role of myosin Va in secretory granule trafficking and exocytosis

Abstract: It emerges that myosin Va plays multiple roles in the trafficking of SGs (secretory granules). In addition to a function in the capture and transport of newly formed SGs in the F-actin-rich cortex, myosin Va is implicated in late transport events of these organelles, which precede their exocytosis. Consistent with these roles, interactions of myosin Va with an array of well-known proteins involved in regulated protein secretion have been documented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 42 publications
1
35
0
Order By: Relevance
“…Even though Myo5a has been implicated in the regulation of secretory vesicle trafficking its interaction with Rab3A had not been established previously. Studies of Myo5a in different cell types shows that this motor is involved in the capture of vesicles and their actin-based transport, as well as in late steps in exocytosis (56). Thus, our results support the idea that GTP-bound Rab3A is involved in Myo5a-dependent vesicle transport.…”
Section: Discussionsupporting
confidence: 80%
“…Even though Myo5a has been implicated in the regulation of secretory vesicle trafficking its interaction with Rab3A had not been established previously. Studies of Myo5a in different cell types shows that this motor is involved in the capture of vesicles and their actin-based transport, as well as in late steps in exocytosis (56). Thus, our results support the idea that GTP-bound Rab3A is involved in Myo5a-dependent vesicle transport.…”
Section: Discussionsupporting
confidence: 80%
“…Myosin-Va has a role in different aspects of the traffic of several vesicular carriers (Desnos et al, 2007;Eichler et al, 2006). It has been shown to be important in retaining these vesicular carriers (melanosomes, secretory granules) in the F-actin-rich cortex (Rudolf et al, 2003;Wu et al, 1998), and recently a role in fusion and exocytosis has also been reported via the interaction of myosin-Va with syntaxin-1A (Watanabe et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…MyoVa has been implicated in transport of secretory granules and melanosomes to the cell surfaces of neuroendocrine cells (6,22) and melanocytes, respectively (36). Through the use of two different dominant negative myosin Va (DNmyoVa) constructs lacking the actin-binding domain but con- HSV alters the conformation of myoVa as indicated by a substantial increase in immunostaining with a myoVa-specific polyclonal antibody starting at about 4 hpi with HSV-1 (Fig.…”
Section: Discussionmentioning
confidence: 99%